Acta Geotechnica - Acta Geotechnica (Springer Nature, 2026)
"Acta Geotechnica" is an international journal devoted to the publication and dissemination of basic and applied research in geoengineering – an interdisciplinary field dealing with geomaterials such as soils and rocks. Emphasis is placed on the interplay between the geomechanical models and their engineering applications.
FI 1.45
Q1
Keywords: Physical Sciences & Engineering; Geoengineering; Geoingeniería; Acuerdos transformativos; Transformative agreements; Geomateriales; Riesgos geológicos